SCREEN DESIGN IMPROVEMENT SYSTEM (SDIS): SYSTEM FOR ASSISTING STUDENTS IN SCREEN DESIGN PROCESS - Abdullah, Zaleha; Junaidi, Juhazren; Atan, Noor Azean (Persatuan Teknologi Pendidikan Malaysia, 2007)
Visual is seen as a powerful tool to deliver information. An effective visual or a good production of screen design requires creativity and some design knowledge. Does this mean only designers are capable to come out with quality design? How about educators? Majority of educators do not possess any art or design background. In reality, an educator who provides visuals as a means of communication in the computer based learning process need to be able to produce visual design that are visually literate. Creative learning process helps to promote creativity. Screen designing work involves creative thinking and creativity can be trained using various methodologies or process. According to creativity expert Dr. R. Keith Sawyer, 2006- creativity is not some magical trait, it took lots of hard work. Creativity is a set of skills that can be learned, developed and used in daily life. The study explores primarily two important aspects. (1) How to improve non-designer (educators) screen design capability? (2) How to create creative learning process through online collaboration? For this reason, prototype of Screen Design Improvement System (SDIS) will be developed based on the Knowledge Creation Model and the Eight specific tasks of Genex Creativity framework. SDIS will go through evaluation phase to verify its capability. Samplings are the final year students from faculty of education, UTM. They are required to produce digital teaching and learning modules in multimedia classes which involve a lot with screen designing. Unfortunately, most of the students are having difficulty to come out with a quality design. They are future teachers in the field of mathematic, physic, chemistry, Islamic studies and English.